Energetics of Spinels in the FeTiO System at the Nanoscale. Issue 16 (1st September 2014) - Lilova, Kristina I.; Pearce, Carolyn I.; Rosso, Kevin M.; Navrotsky, Alexandra
Abstract The energetics of nanosized Fe/Ti spinel oxides was studied using high‐temperature oxide melt solution calorimetry. The mixing properties of the solid solution in the system were obtained, and through comparison to macroscopic materials the effect of particle size on the thermodynamics was assessed. The surface energies of the nanosized materials are similar within the errors regardless of the composition, and are consistent with those determined for other spinels. The enthalpies of oxidation to hematite plus rutile of the iron titanium spinels follow a linear trend with the Fe2+ content, which allows them to be calculated for any composition or particle size. The heat of formation of the macroscopic and nanosized titanomagnetites was fit as a polynomial function and the numerical coefficients are presented. The enthalpies of mixing in the titanomagnetite and titanomaghemite solid solutions are similar at the macroscopic and nanoscale.